Implementation method of waqf in the economic sector: a case study of Waqf Perak Ar-Ridzuan (WPAR) / Farah Dahliah Mustaffa Kamal - Mustaffa Kamal, Farah Dahliah (2022)
The practice of waqf is one of the most demanded practices in Islam. This is because waqf is a type of charity with unique characteristics such as permanence and continuity. The waqf property might benefit the beneficiaries for years, generations, or perhaps centuries. The ownership of waqf is taken away from the owner and returned to Allah for the benefit of His subjects who have been bequeathed the property. Waqf is a type of worship dedicated to Allah that has made a substantial contribution to economic growth by serving as a wealth redistribution mechanism. Next, waqf in Perak is managed by Wakaf Perak Ar-Ridzuan (WPAR) under the Majlis Agama Islam dan Adat Melayu Perak (MAIAMP). Therefore, this study aims to analyse the method of implementation of waqf in the economic sector in Perak. There are three objectives that need to be achieved in this study, namely the first, to identify how the implementation of waqf in the economic sector in the state of Perak. Second, to identify the development of waqf in the economic sector in Perak and the third is to find out how for the public to perform waqf in the economic sector. In addition, to ensure that the objectives of this study are achieved, researchers will use two data, namely primary data and secondary data to obtain information. Primary data was obtained from interviews with respondents while secondary data was obtained from books, internet, journals, newspapers and so on. The respondent who has collaborated in the success of this study is Encik Munawir bin Mohamed Noh, a Manager of the Property and Waqf Management and Development. The results of the data obtained from him were analysed according to the content analysis method and described in chapter 4. The results of the study found that WPAR implemented two waqf projects in the economic sector, namely the waqf boat project and waqf business centre project. In this way, the economy of Muslims can grow and develop.